THE INFLUENCE OF THE SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) LEARNING MODEL ON STUDENTS' CRITICAL THINKING ON GLOBAL WARMING MATERIALS - Jefnita Sain Waruwu; Binari Manurung (ISER (Indonesian Science Education Research), 2022)
In the 21st century, the education sector, especially in the science field, needs to develop facets of teaching methods, learning materials, and assessment strategies to prepare students to have creative thinking and ability to think critically. This study aims to determine the impact of the SETS (Science, Environment, Technology, and Society) learning model on students' critical thinking skills. This study used a quasi-experimental design as the research method and two-group pre-test and post-test testing as the instrument. The study population consisted of seventh grade students 5th Junior High School Percut Sei Tuan, with a sampling technique used cluster random sampling, making students of grades VII3 and VII4 the samples of this study. The results of this study showed that providing a SETS (science, environment, technology and society) model has a very significant effect for teaching critical thinking to students about global warming material in class of seventh grade students country 5 Junior High School Percut Sei Tuan.The thing that can be developed from this research by further researchers is to add media that can support the SETS learning model to get better results